Incidence and clinical predictors of subsequent atrial fibrillation requiring additional ablation after cavotricuspid isthmus ablation for typical atrial flutter. (4th May 2017) - De Bortoli, Alessandro; Shi, Li-Bin; Ohm, Ole-Jørgen; Hoff, Per Ivar; Schuster, Peter; Solheim, Eivind; Chen, Jian
Abstract: Objectives: We sought to investigate the incidence of atrial fibrillation after catheter ablation for typical atrial flutter and to determine the predictors for symptomatic atrial fibrillation that required a further additional dedicated ablation procedure. Design: 127 patients underwent elective cavotricuspid isthmus ablation with the indication of symptomatic, typical atrial flutter. The occurrence of atrial flutter, atrial fibrillation, cerebrovascular events and the need for additional ablation procedures for symptomatic atrial fibrillation was assessed during long-term follow-up. Results: The majority of patients (70%) manifested atrial fibrillation during a follow-up period of 68 ± 24 months, and a significant proportion (42%) underwent one or multiple atrial fibrillation ablation procedures after an average of 26 months from the index procedure. Recurrence of typical atrial flutter was rare. Ten patients (8%) suffered cerebrovascular events. Earlier documentation of atrial fibrillation (OR 3.53), previous use of flecainide (OR 3.33) and left atrial diameter (OR 2.96) independently predicted occurrence of atrial fibrillation during the follow-up. A combination of pre- and intra-procedural documentation of atrial fibrillation (OR 3.81) and previous use of flecainide (OR 2.43) independently predicted additional atrial fibrillation ablation. Discussion: Atrial fibrillation occurred in the majority of patients after ablation for typical atrial flutter and 42% of them required an additional dedicated ablation procedure. Pre- and intraprocedural documentation of atrial fibrillation together with previous use of flecainide independently predicted atrial fibrillation occurrence and a need for additional ablation. Anticoagulation treatment should be continued in high-risk patients in spite of clinical disappearance of atrial flutter.